Smart grid inspired future technologies : first International Conference, SmartGIFT 2016, Liverpool, UK, May 19-20, 2016, Revised selected papers /: first International Conference, SmartGIFT 2016, Liverpool, UK, May 19-20, 2016, Revised selected papers. ([2016]) - Unknown
No abstract available